A Phosphate and Potassium-Solubilising Aspergillus niger Strain Isolated from Spoiled Rice for Potential Biofertilizer Application (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
This study aimed to screen and isolate efficient fungal strains from spoiled rice with phosphate (P) and potassium (K) solubilisation potential. Screening was conducted using solid and liquid Pikovskaya (PVK) medium with tricalcium phosphate (TCP) as the P source and Aleksandrow (AS) medium with potassium alumino silicate as the K source. Among 12 fungal isolates, 8 exhibited positive solubilisation activity, with phosphate solubilisation index (PSI) ranging from 2.00 to 4.00 cm and potassium solubilisation index (KSI) ranging from 2.00 to 3.50 cm. Based on structural morphology under a light microscope, all of them belong to the Aspergillus species. The SA1 strain demonstrated the highest P and K solubilisation in liquid media, releasing 836.67 µg/mL P (pH 3.55, p < 0.05) and 78.90 µg/mL K (pH 3.57, p < 0.05) after 7 days of incubation at 30°C. The pH reduction was associated with organic acids secretion, primarily gluconic acid (10.09 mg/L for P; 4.58 mg/L for K), followed by citric, oxalic, and lactic acids. The fungal strain SA1 was further identified using ITS region sequencing and was confirmed to be Aspergillus niger. These findings highlight the potential of this fungal strain as biofertilizer to enhance plant growth and improve soil health.
Keywords: Aspergillus niger; Biofertilizer; Phosphate solubilising fungi (PSF); Potassium solubilising fungi (KSF); Screening